THE ANALYSIS OF DIFFERENT CREEL SYSTEMS IN DIRECT BEAMING PLANT - Moekarto Moeliono; Freisch Kohller; Mochamad Furqon; Yusniar Siregar (Arena Tekstil, 2011)
A research of warping machine has been carried out to investigate the performance of direct beamingplant, that using 5 different creels system. Three of yarn count, i.e. tex 36, 30 and 25 was performed and usedwarping machine from Benninger Machinary Ltd. The research was conducted in 3 factories for 4,000 hours in twoshiftoperation that carried out since 2009 to 2010. In addition, 100 % combed cotton material was used.The aim of this research is to get some datas of performance of warping machine i.e., propered machine,efficiency and productivity. Based on that data, the manufacturer can select the best performance from severalwarping machines that will affect production cost on weaving process.The result of experiments show, that for V creel system the batch changing of 30,000 meters for tex yarncount 36, 30, and 25 requires 52,57, and 59 minutes respectively . Then the time of warp processing for these yarncounts, need about 2,098; 2,125 and 2,250 minutes respectively. In addition, the V-creel sistem requires lowernumber of worker for creeling and doffing the packages, beside that a lower cost is also shown in this system i.e.,63.90; 65.23; and 68.11 for yarn count 36, 30 and 25 respectively; also for the total cost include rewinding remnantpackages. It is therefore a good performance has significantly resulted in V-creel system.